2008
DOI: 10.1007/s10165-008-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Vasculo-Behçet’s disease with non-traumatic subcapsular hematoma of the kidney and aneurysmal dilatations of the celiac and superior mesenteric arteries

Abstract: We report a patient with vasculo-Behçet's disease treated successfully with a high dose of prednisolone. In 2002, the patient was diagnosed with vasculo-Behçet's disease. He was admitted to our hospital because of sudden-onset right lower back pain in June 2006. Upon admission, abdominal angiography revealed aneurysmal dilatations of the celiac and superior mesenteric arteries. He was treated promptly with high-dose prednisolone, after which the aneurysms displayed no further enlargement. As we believe this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In 25 cases, the multisystem disorder involved oral aphthosis, 5 22 genital aphthosis, 5 , 6 , 9 , 10 , 12 17 , 19 , 21 , 22 skin lesions, 7 , 10 , 12 , 14 , 16 , 19 ocular lesions, 6 9 , 14 , 15 , 17 , 19 – 21 , 23 vascular involvement, 5 , 9 , 11 , 15 , 17 , 24 and positive pathergy test. 6 , 15 , 16 , 23 The BD symptoms do not necessarily involve or manifest simultaneously. Patient characteristics are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In 25 cases, the multisystem disorder involved oral aphthosis, 5 22 genital aphthosis, 5 , 6 , 9 , 10 , 12 17 , 19 , 21 , 22 skin lesions, 7 , 10 , 12 , 14 , 16 , 19 ocular lesions, 6 9 , 14 , 15 , 17 , 19 – 21 , 23 vascular involvement, 5 , 9 , 11 , 15 , 17 , 24 and positive pathergy test. 6 , 15 , 16 , 23 The BD symptoms do not necessarily involve or manifest simultaneously. Patient characteristics are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, nephrotic syndrome might be present in over 83% of patients with amyloidosis, and renal failure is common at the time of diagnosis [7,8,10]. Other case reports also describe some rare forms of renal involvement in Behçet's disease, such as perirenal haematoma [12], renal microinfarction [13] and nontraumatic subcapsular kidney haematoma [14].…”
Section: Discussionmentioning
confidence: 97%
“…Patients with vasculo-Behcet are at risk of developing recurrent vascular lesions and are prone for progressive multifocal vessel related complications [ 2 ]. Aorta is the most susceptible site to aneurysm, followed by the pulmonary artery, femoral artery, subclavian artery, cervical artery and popliteal artery [ 6 ]. Involvement of the coronary and renal arteries is very rare [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was also actively bleeding ruptured aneurysm on CT images. Zhang et al reported that there was no BD in 165 cases as a cause of non-traumatic renal bleeding [ 6 ]. To our knowledge, there have been no reports of BD both with Budd-Chiari syndrome and multiple microaneurysms in the kidney presented with renal hematoma, and superselective catheterization and embolization of actively bleeding aneurysm, with the same patient.…”
Section: Discussionmentioning
confidence: 99%